2019
DOI: 10.1080/09540253.2019.1632809
|View full text |Cite
|
Sign up to set email alerts
|

How does gendering matter in preschool science

Abstract: This article explores gendered processes in preschool science through Barad's agential realism [2007. Meeting the Universe Halfway. Quantum Physics of the Entanglement of Matter and Meaning. London: Duke Universal Press], and as such, the study makes both theoretical and empirical contributions in how it combines perspectives from emergent science [Siraj-Blatchford, J. 2001. Emergent Science and Technology in the Early Years." Paper presented at the XXIII World Congress of OMEP. Santiago, Chile, August 3], ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One important conclusion from the study is that teachers need to be attentive to how gendering processes co-create if, how, and when scientific phenomena get to make themselves intelligible in different situations to different children (Barad 2007), due to individual children's different (and gendered) opportunities to claim space and co-act with materials in various ways. In the same time, it is also important that teachers are open and attentive to the fact that scientific phenomena can make themselves intelligible to children during the most unexpected (to adults) situations and places (Günther-Hanssen et al 2019), as well as during situations that suddenly and rapidly appear which do not belong to the daily doings, norms or routines of the preschool-just like in the case of Emily and the swing. If it is not taken into consideration that science can be "done" in various ways-that is also ways that not always goes in line with traditional norms connected to science, the false picture could be created that some children, already at preschool age, are more "suitable" for science, while others are created as "less suitable", just as can occur in school and higher education (Brickhouse 2001).…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…One important conclusion from the study is that teachers need to be attentive to how gendering processes co-create if, how, and when scientific phenomena get to make themselves intelligible in different situations to different children (Barad 2007), due to individual children's different (and gendered) opportunities to claim space and co-act with materials in various ways. In the same time, it is also important that teachers are open and attentive to the fact that scientific phenomena can make themselves intelligible to children during the most unexpected (to adults) situations and places (Günther-Hanssen et al 2019), as well as during situations that suddenly and rapidly appear which do not belong to the daily doings, norms or routines of the preschool-just like in the case of Emily and the swing. If it is not taken into consideration that science can be "done" in various ways-that is also ways that not always goes in line with traditional norms connected to science, the false picture could be created that some children, already at preschool age, are more "suitable" for science, while others are created as "less suitable", just as can occur in school and higher education (Brickhouse 2001).…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…According to research, the current gender norms connected to STEM and the arts, respectively, mean that certain kinds of children, students, thinking and doing are recognised by teachers and peers, whereas others are not (e.g. Andersson and Gullberg, 2014;Günther-Hanssen et al, 2020;Risner, 2007). What normative constraints do children face when they are expected to engage with the world scientifically, technologically, artistically, engineeringly and mathematically?…”
mentioning
confidence: 99%
“…Studies ranging over three decades have shown that gendering processes do affect children's everyday life in early childhood education settings (Blaise, 2014;Davies, 1989;Lappalainen and Odenbring, 2020), but most of these studies have focused on social relations and not on children's being and learning in relation to academic disciplines. Nevertheless, there are recent studies which indicate that gendering processes negatively affect girls' opportunities to engage in science (Günther-Hanssen et al, 2020), technology (Stephenson et al, 2021) and engineering (Fleer, 2021) in early childhood education.…”
mentioning
confidence: 99%